Increasing physical activity a practical guide - Rippe, James M. (Boca Raton, FL CRC Press, an imprint of Taylor & Francis Group, LLC, 2021)
"The health benefits of regular physical activity are beyond dispute, yet less than 40% of physicians routinely counsel their patients on the importance of physical activity. Increasing Physical Activity: A Practical Guide equips healthcare practitioners to include physical activity counseling in the daily practice of medicine."--Provided by publisher.
Lifestyle Physical Activity and Health -- Background and Key Physical Activity Concepts -- Physical Activity and Cardiovascular Disease Risk Reduction and Treatment -- Physical Activity and Cancer Prevention and Treatment -- Physical Activity and Women's Health -- Physical Activity and Youth -- Physical Activity and Older Adults -- Physical Activity for Individuals with Chronic Conditions -- Physical Activity, Weight Gain and Obesity -- Physical Activity, Cognition and Brain Health -- The Role of Physicians in Promoting and Prescribing Increased Physical Activity -- Exercise Prescription : Practical Applications -- Overcoming Sedentary Behavior -- Promoting Regular Physical Activity.
Includes bibliographical references and index.
Keywords: Exercise; Physical fitness -- Health aspects; Physical fitness -- Psychological aspects; Health Promotion